2019
DOI: 10.3389/fendo.2019.00719
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR-146a Might Regulate Polarization Transitions of BV-2 Cells Induced by High Glucose and Glucose Fluctuations

Abstract: Microglia are critical in neuroinflammation. M1/M2 polarization transitions of microglial phenotypes determine the states of neuroinflammation and are regulated by multiple pathways, including miRNAs and other epigenetic regulations. This study investigated the polarization transitions of microglia induced by high glucose and glucose fluctuations, and the role of miR-146a in regulating M1/M2 polarization transitions of microglia. BV-2 cells were cultured with 25 mmol/L glucose, 75 mmol/L glucose, and 25 mmol/L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…It has been reported that downregulating the expression of IRAK1 by miR-146a increases M2 polarization in BV-2 cells. 41 In another study, NFAT5 suppresses the macrophage M2 phenotype. 47 Thus, it can be assumed that BMSCs-miR -146a-5p-Exos administration elevates microglial M2 polarization by suppressing the expression of IRAK1 and NFAT5.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It has been reported that downregulating the expression of IRAK1 by miR-146a increases M2 polarization in BV-2 cells. 41 In another study, NFAT5 suppresses the macrophage M2 phenotype. 47 Thus, it can be assumed that BMSCs-miR -146a-5p-Exos administration elevates microglial M2 polarization by suppressing the expression of IRAK1 and NFAT5.…”
Section: Discussionmentioning
confidence: 95%
“…We then identified two critical miR-146a-5p targets upregulated after ICH with pro-inflammatory and macrophages/microglia polarizationmodulated properties: IRAK1 and NFAT5. 40,41 IRAK1 is a kinase that belongs to interleukin-1 receptor-associated kinase (IRAK) family, mediating inflammatory responses in multiple pathological processes. 42 It contributes to the activation of NF-κB signaling pathway which is a wellknown inflammation signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interactions between various brain cell types and the brain microvessel endothelial cells, often termed the neurovascular unit (NVU), are critical to maintaining CNS function. A growing body of the literature has described the impact of diabetes on components of the NVU, including: astrocytes, which are less populous and disconnected from endothelial cells [ 50 ]; pericytes, which are similarly diminished and retracted [ 51 ]; oligodendrocytes, which are decreased in number and short-lived [ 52 ]; microglia, which are abnormally polarized [ 53 ]; and endothelial cells, which are rendered less dense and more permeable [ 54 , 55 , 56 ]. However, very little is known about the impact of glycemic variability on the integrity of the NVU.…”
Section: Impact Of Gv On Central Nervous System Inflammationmentioning
confidence: 99%
“…Exposure to chronic hyperglycemia has been associated with activation of microglia [ 84 ]. Furthermore, when studying the mouse microglial BV-2 cell line, exposure to glucose fluctuations resulted in increased markers of metabolic stress leading to apoptosis and/or autophagy [ 85 ] as well as leading to shifts in microglial polarization to the inflammatory M1 phenotype [ 53 ].…”
Section: Impact Of Gv On Central Nervous System Inflammationmentioning
confidence: 99%